The Influence Of Audio Visual Media On Increasing Adolescent Women's Knowledge About Anemia At Mts N 2 Districk Rejang Lebong - Maharani, Elsa; misniarti, misniarti; Kurniyati, Kurniyati (STIKES Syedza Saintika Padang, 2024)
Intoduction: Adolescent females' primary health issue is anemia, which is brought on by inadequate dietary intake. Teenage girls are more susceptible to iron deficiency anemia as a result of menstruation. It is vital to increase teenage girls' understanding of nutrition through education and campaigns that use teen-friendly tactics, in addition to the government's efforts. Videos are one kind of audio-visual material that is used to provide education, among other media. Method: Pre-experiment research is the research design employed, and quantitative research is the research type. The study used a